1994
DOI: 10.5271/sjweh.1407
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hand dermatoses among Finnish farmers.

Abstract: SUSITAIVAL P, HUSMAN L, HORSMANHEIMO M, NOTKOLA V, HUSMAN K. Prevalence of hand dermatoses among Finnish farmers. Scand J Work Environ Health 1994;20:206-12. OBJECTIVES -The goal of this study was to determine the prevalence and risk factors of hand dermatosis among farmers. METHODS -A questionnaire survey was carried out in a geographically defined sample of the Finnish farming population between the ages of 18 and 64 years (N = 10 847). RESULTS -The one-year prevalence of self-reported hand and forearm derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 13 publications
4
19
2
Order By: Relevance
“…In December 1979 a questionnaire regarding health and w o k was sent to a population of Finnish farmers including all registered farmers between the ages of 18 and 64 years in two municipalities (A and B) (14). Most of the farmers in these two inunicipalities were involved in dairy farlning.…”
Section: Methodsmentioning
confidence: 99%
“…In December 1979 a questionnaire regarding health and w o k was sent to a population of Finnish farmers including all registered farmers between the ages of 18 and 64 years in two municipalities (A and B) (14). Most of the farmers in these two inunicipalities were involved in dairy farlning.…”
Section: Methodsmentioning
confidence: 99%
“…Skin rashes or irritation within the past 3 months were more often reported by California grape (52%) than tomato (19%) workers, but the prevalence of eczematous skin conditions on physical examination (10%) was similar in the groups [McCurdy et al, 1989]. In a study of Finnish farmers, (mainly dairy), the 12-month prevalence of dermatoses was 29% in women and 23% in men [Susitaival et al, 1994]. In the same study, a history of hand eczema was found in 42% of all those reporting dermatoses [Susitaival et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…All subjects were patch tested with the allergen set specified in table 1. Some were additionally patch tested with the rubber and/or fragrance allergen sets.…”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that in Finland the 1-year prevalence of selfreported hand and forearm dermatoses was 16% for the women and 7% for the men [1]. Most of the symptoms are due to contact with chemical agents [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%